Bullying, Victimization, Rejection Sensitivity, and Self- regulation in Positive Development of Adolescents - Shafiq, Sameera; Batool, Sidra (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To explore the interaction of bullying and victimization, rejection sensitivity, and self-regulation on the positive development in adolescents. Methodology: Cross-sectional research was conducted at the Department of Psychology, the University of Gujrat, from June to September 2019. In phase I, Self-Regulation Questionnaire (SRQ), Rejection Sensitivity Questionnaire (RSQ), and Positive Youth Development Inventory (PYDI) were translated in Urdu with the permission of their authors by forward-backward translation method. The pretesting was conducted on 130 adolescents selected from random sampling techniques from the public and private colleges of Sara-i-Alamgir. The scales were found reliable with 0.71,0.83, and 0.85 coefficients, respectively. In phase II, with a stratified random sampling technique, 608 students aged 16 to 19 years with Yamane Formula were selected; after informed consent, Urdu versions of SRQ, RSQ, PYDI, Adolescent Peer Relationship Instrument (APRI), and demographic sheet were given to patients. AMOS-21 version was used to analyze the interaction path among the study variables via a structural equation model. Results: Structure Equation Modeling on the data of 608 students confirmed the validity of the model as it was found significant with the p-value <0.001. The model fit indices (CMIN/DF=2.32, CFI=0.99, AGFI= 0.97, GFI, 0.99, TLI=0.98, RMSEA- 0.04, & RMR =0.66) were obtained in acceptable range. Conclusion: The buffering effect of self-regulation plays a significant role in the development of adolescents’ personalities positively while safeguarding them against the impact of bullying, victimization, and rejection sensitivity. Keywords: Adolescent Health, Bullying, Personality Development.